2017
DOI: 10.4103/1008-682x.186884
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer prediction using the random forest algorithm that takes into account transrectal ultrasound findings, age, and serum levels of prostate-specific antigen

Abstract: The aim of this study is to evaluate the ability of the random forest algorithm that combines data on transrectal ultrasound findings, age, and serum levels of prostate-specific antigen to predict prostate carcinoma. Clinico-demographic data were analyzed for 941 patients with prostate diseases treated at our hospital, including age, serum prostate-specific antigen levels, transrectal ultrasound findings, and pathology diagnosis based on ultrasound-guided needle biopsy of the prostate. These data were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…The prostate cancer model showed the highest predictive performance for the optimal models (AUC > 0.80), which is similar to the results obtained in a study using random forest in which an AUC > 0.80 was achieved [ 47 ]. In this study, it was also reported that age was the most contributing variable.…”
Section: Discussionsupporting
confidence: 85%
“…The prostate cancer model showed the highest predictive performance for the optimal models (AUC > 0.80), which is similar to the results obtained in a study using random forest in which an AUC > 0.80 was achieved [ 47 ]. In this study, it was also reported that age was the most contributing variable.…”
Section: Discussionsupporting
confidence: 85%
“…RF adopts the concept of integrated learning to synthesize the classification results of each decision tree to prevent over-fitting, thus yielding more accurate and stable results. Xiao et al [19] used the RF method to construct a diagnostic model for prostate cancer with an accuracy of 83.1%, a sensitivity of 65.6%, and a specificity of 93.8%. Casanova et al [20] compared the diagnostic performances of logistic regression and RF for the diagnosis of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that sepsis patients with active cancer, when compared to those without active cancer, were predominantly younger in age and were less likely to have chronic illnesses such as diabetes mellitus, hypertension, coronary artery disease, chronic obstructive pulmonary disease and stroke. Although older patients have a higher incidence and a higher prevalence of malignancy in general [ 28 32 ], they are also more likely to receive home hospice care compared to younger cancer patients in Taiwan [ 33 ]. We presumed this difference made our cancer patients admitted to ICU younger and had less chronic comorbidities.…”
Section: Discussionmentioning
confidence: 99%